The importance of pragmatics in Linguistics (Journal of Universal Science Research, 2023)
Pragmatics as a field of study has a rich history, and its recognition as a significant approach to language learning and understanding began to gain prominence in the mid-20th century. In linguistics, the study of pragmatics focuses on how context influences the interpretation of meaning in language. This includes aspects such as speech acts, implicature, presupposition, and discourse analysis, all of which are crucial for effective communication. While the theoretical foundations of pragmatics can be traced back to philosophers such as Charles Peirce and Charles Morris in the late 19th and early 20th centuries, the systematic study of pragmatics as a distinct linguistic discipline gained momentum in the 1960s and 1970s.